GE_GERICHTE P/16113/2020 vom 29. September 2020 - GE Cour de justice (2020)
CALOMNIE;VIOLATION DU DEVOIR D'ASSISTANCE OU D'ÉDUCATION;MISE EN DANGER DE LA VIE D'AUTRUI(ART. 129 CP) | CP.174; CP.129; CP.219